Combined effects of polyethylene and organic contaminant on zebrafish (Danio rerio): Accumulation of 9-Nitroanthracene, biomarkers and intestinal microbiota. (15th May 2021) - Zhang, Jinghua; Meng, Han; Kong, Xiangcheng; Cheng, Xinying; Ma, Tao; He, Huan; Du, Wenchao; Yang, Shaogui; Li, Shiyin; Zhang, Limin
Abstract: Microplastics, as emerging pollutant, are predicted to act as carriers for organic pollutants, but the carrier role and bio-toxic effects with other pollutants in environments are poorly acknowledged. In this study, both the single and combined effects of polyethylene (PE, 10 and 40 mg/L) with the particle size of 100–150 μm and 9-Nitroanthracene (9-NAnt, 5 and 500 μg/L) on zebrafish ( Danio rerio ) had been investigated. The results illustrated that PE could be as 9-NAnt carrier to enter into zebrafish body, but significantly reduced the bioaccumulation of 9-NAnt, due to the occurrence of adsorption interactions between the simultaneous presence of both PE and 9-NAnt. After 4 days, the enzymes activity of cytochrome P4501A, acetylcholinesterase (AChE), superoxide dismutase (SOD), catalase (CAT), lactate dehydrogenase (LDH), and the abundance of malondialdehyde (MDA), lipid peroxide (LPO) responded strongly to low-dose PE exposure (10 mg/L). After 7 days exposure to PE-9-NAnt (40 mg/L), the P4501A activity increased significantly, but the activities of AChE and LDH were inhibited clearly, causing certain neurotoxicity and disorders of energy metabolism to zebrafish. The analysis of integrated biomarker response index (IBR) suggested that PE had greater bio-toxicity to zebrafish in all exposure groups after short-term exposure, but the PE-9-NAnt complex showed greater bio-toxicity after 7 days, which indicated that complex exposure of PE-9-NAnt had a delayed effect on the bio-toxicity of zebrafish. Furthermore, analysis of the intestinal microbiota exhibited that under the conditions of the exposure group with 9-NAnt, the relative abundance of the five dominant bacterial phyla (Proteobacteria, Firmicutes, Fusobacteriota, Bacteroidota and Verrucomicrobiota) changed greatly. Overall, this study confirmed that PE could carry 9-NAnt into fish causing bioaccumulation, but in the case of coexisting exposures, PE reduced 9-NAnt bioaccumulation, suggesting that microplastics with other emerging pollutants in chronic toxicity are probably next objects in future works. Graphical abstract: Image 1 Highlights: PE acted as a vector for carrying 9-NAnt enter and accumulate in zebrafish. PE brought about more severe neurotoxicity and oxidative stress than 9-NAnt and PE-9-NAnt complex. PE-9-NAnt complex had a delayed effect on the biological toxicity of zebrafish. The accumulation of 9-NAnt in zebrafish strongly changed the compositions of the intestinal microbial community. Abstract : The bioaccumulation of 9-NAnt, strongly influenced by PE, caused limited bio-toxicity to zebrafish, but significantly changed the composition of intestinal microbiota.